New Hubula Male Model of the Dani Tribe After Cultural Acculluration in Jayawijaya District, Papua - Yanuarius You (Budapest International Research and Critics University, 2022)
This study aims to evaluate the change in the perspective of new men on gender relations between men and women in the Hubula Dani tribe after cultural acculturation occurred. This study uses a descriptive qualitative method with a case study approach to the Hubula Dani community in Aso Lokobal District, Jayawijaya Regency, Papua. The research data consisted of primary data obtained directly from the field through field observations, in-depth interviews, and Focus Group Discussions (FGD), and secondary data obtained from various documents related to the research topic. Data were analyzed by descriptive qualitative technique. The results showed that the new pro-feminist and egalitarian men in the Hubula Dani community began to be more modern and open to progress as a positive impact of cultural acculturation through the influence of the Catholic church, local government, and educational institutions. They have authority as husbands who are responsible for the family as breadwinners in the nuclear family. They want to share or help the wife's role at home; give the wife access and control over resources; willing to help his wife take care of the children; respecting the wife's abilities and giving her the opportunity to work outside the home; avoid violence against wives but if violence does occur they do not overdo it and resolve the issue amicably; begin to be critical of non-egalitarian customs; willing to have many children as a joint decision; and provide equal opportunities for boys and girls to achieve higher levels of education.